IMPLEMENTATION OF DIGITAL DATA COLLECTION FOR COGNITIVE PERFORMANCE IN THE LONG LIFE FAMILY STUDY. (11th November 2018) - Andersen, S L; Wojczynski, M K; Glynn, N W; Thyagarajan, B; Mengel-From, J; Au, R; Perls, T T; Cosentino, S
Abstract: The Long Life Family Study, a longitudinal study of healthy aging among families with clustering for longevity, is a valuable cohort for identifying early markers of cognitive change. As digital metrics of cognitive performance may be more sensitive to cognitive change, we sought to implement a digital layer of data collection beyond standardized neuropsychological testing procedures. We used a digital voice recorder to capture spoken responses and a digital pen for written responses. The digital pen is a ballpoint pen with a digital camera that records the time-stamped pen position on coded paper creating a movie of the participant's drawing process. The devices were low cost and usable by participants who are unfamiliar with digital technologies. The digital data allow for additional quality control, extraction of voice and graphomotor characteristics (e.g., prosody and tremor), and isolation of cognitively demanding task components from overall test performance (e.g., decision-making latencies).